Workload, time-on-task, and learning outcome in online learning for beginning students - Tobias Kärner; Marc Egloffstein; Florian Binöder; Clemens Frötschl; Thomas Schley (Forum Neue Medien in der Lehre Austria, 2015)
Online learning offers great potential for higher education in terms of scalability, flexibility and instructional design. However, the suitability of open online formats for beginning students is open for discussion. In this paper, we thus describe beginning students' learning processes in an open online course within a longitudinal workload study. All in all, 238 students were surveyed continuously over one semester via diary method, which led to an overall collection of 10,540 individual activities. Results indicate that the students' actual workload was consistently lower than the intended target workload, and that it was also unevenly distributed. In line with existing research, a weak positive association between time-on-task and learning outcome was found. Implications for the course design and follow-up research are discussed. 16.12.2015 | Tobias Kärner, Marc Egloffstein, Florian Binöder, Clemens Frötschl & Thomas Schley (Bamberg, Mannheim)